Overexpression of a Plasma Membrane Bound Na+/H+ Antiporter-Like Protein (SbNHXLP) Confers Salt Tolerance and Improves Fruit Yield in Tomato by Maintaining Ion Homeostasis - Kumari, P. Hima; Kumar, S. Anil; Sivan, Pramod; Katam, Ramesh; Suravajhala, Prashanth; Rao, K. S.; Varshney, Rajeev K.; Kishor, Polavarapu B. Kavi (Frontiers in Plant Science, 2017)
A Na+/H+ antiporter-like protein (NHXLP) was isolated from Sorghum bicolor L. (SbNHXLP) and validated by overexpressing in tomato for salt tolerance. Homozygous T2 transgenic lines when evaluated for salt tolerance, accumulated low Na+ and displayed enhanced salt tolerance compared to wild-type plants (WT). This is consistent with the amiloride binding assay of the protein. Transgenics exhibited higher accumulation of proline, K+, Ca2+, improved cambial conductivity, higher PSII, and antioxidative enzyme activities than WT. Fluorescence imaging results revealed lower Na+ and higher Ca2+ levels in transgenic roots. Co-immunoprecipitation experiments demonstrate that SbNHXLP interacts with a Solanum lycopersicum cation proton antiporter protein2 (SlCHX2). qRT-PCR results showed upregulation of SbNHXLP and SlCHX2 upon treatment with 200 mM NaCl and 100 mM potassium nitrate. SlCHX2 is known to be involved in K+ acquisition, and the interaction between these two proteins might help to accumulate more K+ ions, and thus maintain ion homeostasis. These results strongly suggest that plasma membrane bound SbNHXLP involves in Na+ exclusion, maintains ion homeostasis in transgenics in comparison with WT and alleviates NaCl stress.